Automatic Detection System for Surface Defects of Test Subjects Based on Machine Vision - KIM, NAM HO; LEE HYUN JUN; JEONG, HEE JA (2024)
An object of the present invention is to improve the stability of the inspection quality of a target object and the sensitivity of defect detection to enable rapid response to defects, and to ensure the diversity of inspection items of the target object. The present invention comprises: a barcode scanner for reading barcode data for each model of a target object; a vision inspection device for photographing and inspecting the front and side surfaces of the target object; a front inspection data processing device for processing front inspection data of the target object inspected by the vision inspection device; a side inspection data processing device for processing side inspection data of the target object inspected by the vision inspection device; a control device; and an inspection data storage device for storing inspection data including whether the target object is good or defective generated by the control device. The present invention has the advantage of reducing the time and cost of recombination of process variables. 본 발명은 피검사체의 품질관리를 위하여 피검사체를 특정 위치에서 촬영한 후 영상데이터를 획득하고, 비전검사 알고리즘에 따라 촬영한 이미지와 설계데이터 값을 비교 및 분석하여 피검사체의 찍힘, 긁힘, 교정자국 및 변형 또는 이물질 검출 등 피검사체의 불량 여부를 판단할 수 있는 머신비전 기반 피검사체 표면 결함 자동 검출 시스템에 관한 것으로, 피검사체의 모델별 바코드데이터를 읽어 들이는 바코드스캐너; 상기 피검사체의 전면 및 측면을 촬영하여 검사하는 비전검사장치; 상기 비전검사장치에서 검사한 피검사체의 전면 검사데이터를 처리하는 전면 검사데이터 처리장치; 상기 비전검사장치에서 검사한 피검사체의 측면 검사데이터를 처리하는 측면 검사데이터 처리장치; 상기 피검사체의 바코드데이터와 전면 검사데이터 및 측면 검사데이터를 비전검사 알고리즘의 수행으로 피검사체의 불량 여부를 비교 판단하여 양품 또는 불량품 검사데이터를 생성하고, 피검사체를 검사하는 검사설비를 제어하며, 피검사체의 검사결과를 가시적인 정보데이터로 표출하는 표시장치를 제어하고, 불량품으로 판정된 피검사체를 제거하는 불량품 제거장치를 제어하는 제어장치; 상기 제어장치에서 생성된 피검사체의 양품 또는 불량품 여부를 포함하는 검사데이터를 저장하는 검사데이터 저장장치를 포함하여 이루어진 것이다. 본 발명은 스마트팩토리 제조공정의 품질관리를 위한 것으로, 라인 스캔 카메라를 이용한 비전검사를 통하여 피검사체의 품질향상 및 불량품을 감소시키고, 비전검사 알고리즘으로 피검사체의 양산 및 품질 안정화를 위한 기간을 단축시킬 수 있으며, 공정의 최적화에 따른 사이클 타임을 단축시킬 수 있고, 생산 및 검사 정보의 빅데이터화가 가능한 것이다.